A Low Cost Large‐Area Solid Oxide Cells Fabrication Technology based on Aqueous Co‐Tape Casting and Co‐Sintering. Issue 4 (2nd May 2014) - Zhou, J.; Liu, Q.; Sun, Q.; Hwa Chan, S.
Abstract Aqueous‐based tape casting is a low‐cost and environment friendly technology. In this paper, large‐area fuel electrode‐supported solid oxide cells (SOCs) were fabricated by this technology in conjunction with co‐sintering process. A 10 cm × 10 cm single cell with NiO/Zr0.92Y0.08O2–δ fuel electrode, Zr0.92Y0.08O2–δ electrolyte and La0.6Sr0.4Co0.2Fe0.8O3+δ/Ce0.9Gd0.1O2+δ air electrode has been successfully developed with improved electrode microstructure and hence the cell performance with the maximum power density of 534 mW cm–2 at 850 °C with humidified H2 as the fuel and air as the oxidant has been achieved. The optimal slurry formulations used in the fabrication of SOC were summarized for future reference purpose.